Aproveitamentos de rupturas estéticas de vanguarda em contos de Rubem Fonseca - Freitas, Gabriel Domício Medeiros Moura (2012)
We analyze here how the vanguard historical movement radical critics to the organic concept of artwork, which is made with all the parts being related to each other and according to some unit´s notion, are configured in five Rubem Fonseca´s short stories: O Quarto Selo (Fragmento) (1969), Passeio noturno (Parte I) (1975), Passeio noturno (Parte II) (1975), Livro de ocorrências (1979) e O Cobrador (1979). In this way, our work´s first chapter is about Plato (2006) and Aristotle (1993) philosophical thesis on esthetics and the important differences among each one´s concepts about this subject. Afterwards, we discuss about the esthetical ruptures promoted by vanguards both in Europe and in Brazil along 20th century´s beginning. For this purpose, subjects like vanguard´s origin, its triumph, the main contributions to later periods and the crisis faced by that paradigm will be discussed. In the second chapter, the unsatisfactory definitions about short stories are the object of our discussion. We begin the considerations related to this subject discussing Poe´s (1999) ideas found on his Filosofia da composição and their acritical reception by later authors such as Cortázar (1974) and Moisés (1978), who are also discussed further. Finally, Piglia´s (2004) trying to define short story is discussed with the necessary problematizations. Otherwise, in the third chapter, we develop analysis relative to the narratives mentioned before, searching not only how vanguards´ esthetical ruptures are singularly configured in each case, but also verifying these narrative procedures functionality as they deal with the relation among form and subject found in every single narrative chosen. To achieve this last aim, we recollect contributions from Kermode (1997), Mangueira (2003), Figueiredo (2003), Gil (2008), Schwarz (1992, 1999), Pasta Jr. (1999, 2010) and some other authors.